Optimalisasi Pembelajaran Berbasis Budaya dalam Menumbuhkan Apresiasi Siswa terhadap Pangan Lokal Garut melalui Strategi City Branding - Pelapory, Khirst David; Nurwahidah, Lina Siti; Hamdani, Agus (PGSD Universitas Muria Kudus, 2025)
This study aims to describe the improvement of eleventh-grade studentsâ€™ appreciation of Garut local food (dodol, burayot, and lunkhead) through culturally responsive teaching integrated with city branding strategies at SMAN 11 Garut. A culture-based approach is used to integrate Garut's local cultural values into the learning process, while city branding is utilized to promote regional culinary identities, such as dodol, burayot, and lunkhead.This qualitative case study involved 30 students in an eight-week intervention. Data were collected through participatory observation, semi-structured interviews, student project analysis (posters, videos, Instagram campaigns), and focus group discussions. Thematic analysis was performed using six-phase framework with NVivo 14 software. The findings revealed three main themes: (1) enhanced understanding of cultural and nutritional values (87% of students), (2) high creativity in city branding promotion (73% of projects scored â‰¥4 on a 5-point scale), and (3) increased regional pride and active promotional behaviour (93% of students). The integration proved effective in preserving Garutâ€™s culinary heritage and strengthening its identity as â€œKota Dodolâ€.Â